Sydenham's Chorea; Clinical and Magnetic Resonance Imaging Findings, a Retrospective Observational Study in Children - Hanci, Fatma; Hizal, Mustafa; Türay, Sevim; Kalaycioğlu, Oya; Kabakuş, Nimet (Journal of Pediatric Neurology, 2020)
The purpose of this study was to evaluate the correlation between magnetic resonance imaging (MRI) findings and demographic and clinical characteristics, response to treatment times, and recurrence rates of Sydenham's chorea (SC), the most common of the acquired pediatric choreas. The clinical and radiological findings of 12 patients presenting to the pediatric neurology clinic in the previous 4 years and diagnosed with SC on the basis of the modified Jones criteria were investigated retrospectively from the hospital files. In addition, we measured the maximum prefrontal cortex and basal ganglia (globus pallidus, putamen, and caudate nucleus) thicknesses in the axial plane from patients' cerebral MRIs and compared these values with prefrontal cortex and basal ganglia thicknesses of a healthy control group measured using the same technique. Patient and control groups' cranial and basal ganglia MRIs were found to be normal. However, patients' globus pallidus thicknesses were significantly lower than those of the healthy control group. Additionally, the globus pallidus values of patients with recurrent SC and a prolonged healing time were lower than average. However, we determined no significant difference in terms of prefrontal motor cortex, caudate nucleus, or putamen thicknesses between the patient and control groups. Low globus pallidus thicknesses in patients with SC may indicate atrophy associated with globus pallidus involvement. Further experimental and prospective and long-term studies are needed for a better understanding of the factors affecting the pathophysiology, recurrence, and healing time of SC.
Keywords: basal ganglia; childhood; magnetic resonance imaging; prefrontal motor cortex; Sydenham's chorea